(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The new coronavirus infection COVID-19 is characterized by a multisystem lesion and a high risk of post-infectious complications from internal organs, including the cardiovascular and urinary systems. In a significant proportion of patients, pathological changes are subclinical in nature and are not detected at early stages using standard clinical and laboratory research methods.